Fecal microbiota transplantation therapy in Crohn's disease: Systematic review. Issue 10 (6th July 2021) - Fehily, Sasha R; Basnayake, Chamara; Wright, Emily K; Kamm, Michael A
Abstract: Background: The gastrointestinal microbiota is the key antigenic drive in the inflammatory bowel diseases. Randomized controlled trials (RCTs) in ulcerative colitis have established fecal microbiota transplantation (FMT) as an effective therapy. We have conducted a systematic review to evaluate the efficacy of FMT in Crohn's disease. Methods: A systematic literature search was performed through to August 2020 (MEDLINE; Embase). Studies were included if they reported FMT administration in patients with Crohn's disease, and reported on clinical outcomes. Results: Fifteen studies published between 2014 and 2020, comprising 13 cohort studies and two RCTs, were included in the analysis. The majority of trials evaluated FMT for induction of remission, with follow‐up duration varying from 4 to 52 weeks. One RCT in 21 patients, of single‐dose FMT versus placebo, following steroid‐induced remission, showed a higher rate of steroid‐free clinical remission in the FMT group compared to the control group: 87.5% vs 44.4% at week 10 ( P = 0.23). Another RCT, two‐dose FMT in 31 patients, showed an overall clinical remission rate of 36% at week 8, however, with no difference in clinical or endoscopic endpoints between FMT administered by gastroscopy and colonoscopy. Considering all studies, the clinical response rates in early follow up were higher following multiple FMT than with single FMT. FMT dose did not appear to influence clinical outcomes, nor did whether FMT was fresh or frozen. FMT delivered via upper gastrointestinal route demonstrated higher early efficacy rates of 75 to 100% compared with lower delivery route rates of 30% to 58%, but on follow up beyond 8 weeks, this difference was not maintained. Whether pre‐FMT antibiotic administration was beneficial was not able to be determined due to the limited number of patients receiving antibiotics and varying antibiotic regimens. No serious adverse events were reported. Conclusions: Preliminary studies suggest that FMT may be an effective therapy in Crohn's disease. However large controlled trials are needed. No serious safety concerns have been identified.